Desempenho e características de carcaça de codornas de corte em função da idade da matriz, peso do ovo e nível nutricional - Andre Brito Correa (2010)
Four experiments were undertaken to evaluate the effect of breeder age, and egg weight on performance and carcass traits, and two other experiment to evaluate the effect of crude protein level on the performance, carcass traits and intestinal morphometric traits of two genetic groups of meat type quails (EV1 and EV2). In experiment 1 and 2, quails from heavier egg weight and from 205 and 280 days breeder age classes showed higher performance. Heavier egg weight resulted in heavier quails at hatch. Quails from 205 and 280 days breeder age classes and from 13.0-14.9g and 15.0-16.9g egg weight classes were heavier and had higher carcass weight at 42 days of age. In experiments 3 and 4, the correlation estimates between weights at different ages suggest body weight at 21 days of age is highly correlated with slaughter body weight In experiments 5 and 6, the estimated crude protein level of diet for maximum performance of quails from hatch to 21 days of age was 33.0% for both genetic groups and from hatch to 42 days of age were 29.38% and 28.8% for EV1 and EV2 genetic groups, respectively. Crude protein levels significantly affected the villous jejunum and duodenum area and density of EV1 genetic group and villous ileum and duodenum volumes and areas of EV2 genetic group.